2002
DOI: 10.1097/00005176-200210000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease in India: Are They True Cases of Celiac Disease?

Abstract: Indian children with CD are true cases of CD. They present late, diarrhea is absent in 20% of cases, and AGA test results show 88% of children without false-positive results at a cutoff value of 10 U/mL. However, AGA test with 94% sensitivity at a cutoff value of 5 U/mL can be used as screening test to select suspected cases for further workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…Most of the subsequent reports on CD came from the northern part of India (States of Punjab, Haryana, Delhi, Rajasthan, Uttar Pradesh), where wheat is the staple dietary cereal [6,7,8,9,10,11,12,13,14,25,26,27,28]. …”
Section: Celiac Disease In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the subsequent reports on CD came from the northern part of India (States of Punjab, Haryana, Delhi, Rajasthan, Uttar Pradesh), where wheat is the staple dietary cereal [6,7,8,9,10,11,12,13,14,25,26,27,28]. …”
Section: Celiac Disease In Asiamentioning
confidence: 99%
“…Although there has been an increase in the number of publications on CD from the Asian region, there is a paucity of literature on its prevalence in most Asian nations, with the exception of India [6,7,8,9,10,11,12,13,14]. Additionally, few case reports and short reports are available from China, Pakistan and Japan [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia and short stature were more in comparison to Western studies, thereby reflecting delayed diagnosis [4]. However, short stature is less as compared to previous Indian study published a decade ago [5]. There is ongoing need to increase the awareness about the different presentations of the disease so as to enable early diagnosis.…”
mentioning
confidence: 92%
“…A study done by Patwari A. K. et al had shown that the mean age at the time of presentation was 6.67+ 2.37 years [23] . In a study by Poddar U et al mean age of 50 children with celiac disease was 6.3 + 2.6 years [24] . Result of our study in term of mean age of presentation are comparable with above mentioned studies.…”
Section: Discussionmentioning
confidence: 93%